2021
DOI: 10.1002/adsc.202100951
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Mediated Synthesis of Sulfonyl Fluorides from Arylazo Sulfones

Abstract: Sulfonyl fluorides are useful motifs for a wide range of applications in organic synthesis including sulfur (VI) fluoride exchange-based "click chemistry." Herein, a visible-light-mediated synthesis of sulfonyl fluorides from arylazo sulfones is described. In the present study, K 2 S 2 O 5 and N-fluorobenzenesulfonimide (NFSI) were used as the sulfonyl source and fluorinating agent, respectively, for visible-light-mediated fluorosulfonylation of arylazo sulfones to prepare various sulfonyl fluorides in 60-85% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…In recent research, scientists reported direct synthesis processes that did not use metal catalysts or that used photocatalysts that have overcome the above disadvantages, but there are few of these studies. 80,89,93,101 Therefore, there are many opportunities to develop new synthetic methods using visible light to synthesize sulfur dioxide-containing compounds. Discovery of sulfonylation reactions conducted under light without transition metal or photocatalysts as well as identication or creation of new sulfonyl sources and precursors will provide more effective synthesis methods for high-value structures in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent research, scientists reported direct synthesis processes that did not use metal catalysts or that used photocatalysts that have overcome the above disadvantages, but there are few of these studies. 80,89,93,101 Therefore, there are many opportunities to develop new synthetic methods using visible light to synthesize sulfur dioxide-containing compounds. Discovery of sulfonylation reactions conducted under light without transition metal or photocatalysts as well as identication or creation of new sulfonyl sources and precursors will provide more effective synthesis methods for high-value structures in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A single-electron transfer (SET) process between the excited iridium *Ir III In 2022, Kim and co-workers performed a novel sulfonyl-uorination from arylazo sulfones. 80 In this method, arylazo sulfones were reacted with K 2 S 2 O 5 and NSFI in a mixture of MeCN and H 2 O under irradiation of visible light at room temperature without any photocatalyst to prepare sulfonyl uorides (Scheme 14). Reactions of naked arylazo sulfones as well as substrates bearing electron-donating groups such as methoxy and tert-butyl groups were readily carried out to give the corresponding products (51a and 51b) with high yields.…”
Section: S-x Bond Formation Reactionmentioning
confidence: 99%
“…In addition to direct substitution of sulfonyl compounds with fluoride anion, oxidative fluorination has frequently been adopted, as has the use of sulfonyl precursors. For example, N ‐fluorobenzenesulfonimide, [ 13 ] Selectfluor, [ 14 ] and trichloroisocyanuric acid/KF [ 15 ] are well‐documented reagents for oxidative fluorination. Sulfuryl fluoride (SO 2 F 2 ) is a gaseous fluoride source that has been used with aryl organometallic reagents to prepare aromatic sulfonyl fluorides.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…For this reason, using a well-established methodology, we have synthesized a set of arylazo sulfones (1-14, 16, Figure 2) with compounds bearing various electron-donating and withdrawing groups Recently, our team has extensively studied a class of colored shelf-stable derivatives containing a dyedauxiliary group, namely arylazo sulfones (Ar-N = N-SO 2 -R'). Such derivatives underwent the N-S bond homolysis upon visible light irradiation (Figure 1B, path a) and the ensuing loss of a molecule of nitrogen facilitates the formation of Ar˙and R'-S˙O 2 reactive radicals that have been exploited in the preparation of, among the others, arylstannanes [64], (hetero)arylphosphonates [65], aryl selenides and tellurides [66], symmetrical (hetero)biaryls [67], arylboronates [68], sulfonyl fluorides [69], stilbenes and vinyl sulfones [70], trifluoromethylthiolates [71], and (E)-vinyl sulfones [72]. Additionally, arylazo sulfones were able to initiate the polymerization of a broad range of electron-poor olefins [73], or to cause covalent functionalization (arylation) of reduced graphene oxide nanosheets [74] and simultaneous photografting of both aryl and methanesulfonyl groups on a gold surface [75].…”
Section: Introductionmentioning
confidence: 99%